(3x+5)-(-7x+8)=

Simple and best practice solution for (3x+5)-(-7x+8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+5)-(-7x+8)= equation:


Simplifying
(3x + 5) + -1(-7x + 8) = 0

Reorder the terms:
(5 + 3x) + -1(-7x + 8) = 0

Remove parenthesis around (5 + 3x)
5 + 3x + -1(-7x + 8) = 0

Reorder the terms:
5 + 3x + -1(8 + -7x) = 0
5 + 3x + (8 * -1 + -7x * -1) = 0
5 + 3x + (-8 + 7x) = 0

Reorder the terms:
5 + -8 + 3x + 7x = 0

Combine like terms: 5 + -8 = -3
-3 + 3x + 7x = 0

Combine like terms: 3x + 7x = 10x
-3 + 10x = 0

Solving
-3 + 10x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 10x = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 10x = 0 + 3
10x = 0 + 3

Combine like terms: 0 + 3 = 3
10x = 3

Divide each side by '10'.
x = 0.3

Simplifying
x = 0.3

See similar equations:

| 2y-3x=0 | | 5(3+6x)-5=70 | | -7g=49 | | 4(4x+2)=20-2(x-3) | | x^4-81-x^3+9=0 | | -7(3-x+3)=-18 | | 58q-2.8-5.2q=-0.4-2.2 | | 2x^2-24x+81=0 | | 14x^2+40x-6=0 | | x-7.6=-6.5 | | 12=-24y | | 4x+40=13x-68 | | r+33=14 | | -2t^2-6t+5=0 | | 5y-2+y+48=5y+50-1y | | 5x=165 | | 6x+34=14x+30 | | 3x+139=2x+26 | | y+25y-15y-9y=15-15 | | 2S=2Vt-gt^2 | | 5+x=(3+19x) | | 31+3x=34 | | 6x^2+4x=240 | | 9x+15-7x+15=-2 | | -113=5(5p+3)-3 | | s-44=-13 | | -4(x+5)+3=6(x+4)+1 | | f/2-19=-17 | | 8x-12=68 | | 6q=-6+7q | | 8x=6x+14 | | 5.85=0.65x |

Equations solver categories